Pengaruh Corporate Governance, Karakterstik Perusahaan, dan Kesulitan Keuangan terhadap Pengungkapan Sukarela pada Laporan Tahunan Perusahaan (Studi Empiris pada Perusahaan Manufaktur Yang Terdaftar di Bursa Efek Indonesia Periode 2016-2018) - Endang Purwaningsih; Maria Novita Kurniawati Wibowo (Media Akuntansi, 2020)
This study was to analyze the factors of voluntary disclosure in the annual report listed on Indonesian Stock Exchange. Independent variables were assesed in this study of corporate governance was reflection by the managerial ownership and institutional ownership, characteristic of company was reflection by firm size, profitability and leverage, while the financial distress, dependent variables in this study is voluntary disclosure. The populations was publicly traded manufacturing company listed on the Indonesia Stock Exchange the period 2016 to 2018. Sampling technique was done by purposive sampling. The numbers of populations included in this study as many as 33 companies for a total study sample was 99 annual reports. Type of regression model used in this study is multiple regression using SPSS 19.0. Result of this study indicated managerial ownership, institutional ownership and firm size has significant positive, while the profitability, leverage, and financial distress not significant to voluntary disclosure